System Drug Sales At Pharmacies HUSADA Using Microsoft Visual Basic 6.0 - Supeni Siskawati (Jurnal Manajemen Informatika, 2010)
Information that is valuable information quickly and accurately. So in need of a computerized system asa means of support. System Drug Sales In Pharmacies HUSADA designed with the purpose to obtaininformation quickly and accurately as well as secure data storage. So with the final result which is usefulfor decision making